2018
DOI: 10.5455/ajvs.246155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parity and Milk Production on Conception Rate After Two Synchronization Protocols in Dairy Cows

Abstract: Key words:G6G, Ovsynch, presynchronization, fertility, dairy cow.Our objective in this study the effect of parity and average milk production on the conception rate after resynchronization with G6G protocol or Ovsynch protocol. Lactating Holstein cows (n = 100) divided into two groups (Ovsynch and G6G) cows in this group1 (n = 50) were received the following treatment sequence, 12 µg Buserelin on day zero, 500 µg IM of Cloprostenol on day seven, 12 µg Buserelin IM on day nine and received timed artificial inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Parity has different effects on fertility. According to El‐Razek, Genedy, and Zaghloul (), the conception rate decreases in multiparous cows, after being synchronized with G6G coinciding with Yusuf, Latief‐Toleng, Prawira‐Rahardja, Ako, and Sahiruddin‐ Eriansyah () and the studies of LeBlanc et al (), in which it is suggested that the decrease in the CR is due to the higher risk in multiparous cows of suffering clinical endometritis. Yusuf et al () also suggest that cows with more than four births have more services per conception DeVries, Holtshausen, Oba, and Beauchemin () adds the role of the Negative Energy Balance, which affects more intensively multiparous than primiparous cows.…”
Section: Discussionmentioning
confidence: 99%
“…Parity has different effects on fertility. According to El‐Razek, Genedy, and Zaghloul (), the conception rate decreases in multiparous cows, after being synchronized with G6G coinciding with Yusuf, Latief‐Toleng, Prawira‐Rahardja, Ako, and Sahiruddin‐ Eriansyah () and the studies of LeBlanc et al (), in which it is suggested that the decrease in the CR is due to the higher risk in multiparous cows of suffering clinical endometritis. Yusuf et al () also suggest that cows with more than four births have more services per conception DeVries, Holtshausen, Oba, and Beauchemin () adds the role of the Negative Energy Balance, which affects more intensively multiparous than primiparous cows.…”
Section: Discussionmentioning
confidence: 99%